Bioactive Glass Graft vs Allograft in Benign Bone Lesions: A Retrospective Comparative Study - Incesoy, Mustafa Alper; Sarikas, Murat; Kaya, Hakan Batuhan; Yavuz, Ahmet Durcan; Sulak, Bilal; Ozdemir, Asena Ayca; Ozarslan, Ali Can; Uzer, Gokcer; Yildiz, Fatih; Yucel, Sevil; Gurkan, Volkan (SAGE PUBLICATIONS INC, 2025)
Background: Bioactive glass (BG) is a promising alternative to conventional autogenous and allogeneic bone grafts with osteoconductive, osteoinductive, and antimicrobial properties. The effects of its use in comparison to allograft in the context of benign bone lesions remain less explored.Purpose: We sought to compare the efficacy of 45S5 BG granules to allograft in treating benign bone lesions.Methods: This retrospective study compared the outcomes of 45S5 BG granules and allograft bone in 42 patients undergoing curettage for benign bone lesions. Patients were divided into 2 groups based on the graft material used (n = 21 in each group). Radiological evaluation using the modified Neer classification and functional assessment using the Musculoskeletal Tumor Society (MSTS) score were performed. Complications and time to return to previous activity levels were also recorded.Results: No significant differences were found between the BG and allograft groups in terms of postoperative Neer scores, postoperative MSTS scores, complication rates, or time to return to previous activity levels. Both groups showed significant improvement in MSTS scores over time, although improvement in MSTS scores for both groups did not reach the minimal clinically important difference, suggesting that the observed changes may not be clinically significant.Conclusion: This retrospective study found that BG demonstrated comparable efficacy to allograft cancellous bone in the treatment of benign bone lesions, suggesting that it may serve as a suitable alternative. Further study should focus on longer-term follow-up and larger sample sizes to further elucidate the role of BG in the management of these lesions.
Keywords: bioactive glass; allograft; benign bone lesions; bone graft substitute; comparative study; CYSTS; TUMORS; Orthopedics; Surgery